Pengaruh Komponen Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi Provinsi Nusa Tenggara Barat Tahun 2018-2022 - Irma Ainun Nasyri; Iwan Harsono; Titi Yuniarti; Himawan Sutanto; Ida Ayu Putri Suprapti (UNIVERSITAS SERAMBI MEKKAH, 2024)
The problem in this research is that economic growth in NTB Province fluctuates and is still very low compared to other provinces in Indonesia. This research aims to determine the influence of the components of the human development index, namely Life Expectancy, Expected Years of Schooling, Average Years of Schooling, and Per Capita Expenditure on the Economic Growth of NTB Province. This type of research is based on testing theory through measuring research variables with numbers and in an associative research format. This research is quantitative research using panel data regression analysis tools in the 2018-2022 period per district/city. In this research, the model used is Fixed Effects, because the Fixed Effects model is better than other models, which have been tested using the Chow test and the Hausman test. The data collection technique used is collecting directly from the relevant agency, namely BPS NTB Province. The research results obtained are that, partially, the Life Expectancy variable has a positive and significant effect on Economic Growth, Expected Years of Schooling has a negative and significant effect on Economic Growth, Average Years of Schooling and Per Capita Expenditures do not have a significant effect on Economic Growth. Meanwhile, simultaneously Life Expectancy, Expected Years of Schooling, Average Years of Schooling, and Per Capita Expenditures influence Economic Growth.